IMPLEMENTING THE BALANCED SCORECARD IN STRATEGIC MANAGEMENT OF SHARIA FINANCIAL INSTITUTIONS - Budi Safatul Anam (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
The implementation of the Balanced Scorecard (BSC) in Sharia financial institutions represents a significant evolution in strategic management practices within this sector. This study explores the integration of BSC into the strategic framework of Sharia financial institutions, emphasizing its role in aligning organizational objectives with Sharia principles. Utilizing qualitative methods, including case studies and interviews with industry experts, the research highlights the effectiveness of BSC in enhancing performance measurement and strategic alignment. Findings indicate that institutions employing BSC not only improve operational efficiency but also ensure compliance with Islamic finance principles, thus fostering stakeholder trust. The study concludes that BSC serves as a vital tool for Sharia financial institutions, enabling them to navigate the complexities of the financial landscape while adhering to their ethical mandates. This research contributes to the existing literature by providing empirical evidence on the successful application of BSC in a niche financial sector.